Process control instrumentation technology - Johnson, Curtis D. (Prentice Hall, 1997)
Describing the central systems used in process industries, this edition presents control activities in three categories with greater emphasis on programmable logic controllers, thermal and mechanical sensors, and microprocessors. Material has been added to the measurement systems chapter.